2005
DOI: 10.1017/s1461145705006085
|View full text |Cite
|
Sign up to set email alerts
|

Decreased levels of whole blood glial cell line-derived neurotrophic factor (GDNF) in remitted patients with mood disorders

Abstract: Recent post-mortem and imaging studies provide evidence for a glial reduction in different brain areas in mood disorders. This study was aimed to test whether glial cell line-derived neurotrophic factor (GDNF), a member of transforming growth factor (TGF)-beta superfamily, in blood levels was associated with mood disorders. We measured GDNF and TGF-beta levels in whole blood in remitted patients with mood disorders [n=56; major depressive disorders (MDD) 39, bipolar disorders (BD) 17] and control subjects (n=5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 118 publications
(66 citation statements)
references
References 12 publications
4
60
0
2
Order By: Relevance
“…Furthermore, we recently reported that total GDNF levels in whole blood in patients with mood disorders were significantly lower than those in healthy control subjects (Takebayashi et al, 2006). These results suggest that lower GDNF levels might be involved in the pathophysiology of mood disorders, and increase of GDNF by antidepressants might be involved in their therapeutic action.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, we recently reported that total GDNF levels in whole blood in patients with mood disorders were significantly lower than those in healthy control subjects (Takebayashi et al, 2006). These results suggest that lower GDNF levels might be involved in the pathophysiology of mood disorders, and increase of GDNF by antidepressants might be involved in their therapeutic action.…”
mentioning
confidence: 88%
“…Recent findings showed that several neurotrophic factors such as BDNF, neurotrophin-3, FGF, and GDNF are altered in post-mortem brain, cerebrospinal fluid, or blood from patients with mood disorders (Hock et al, 2000;Shimizu et al, 2003;Evans et al, 2004;Takebayashi et al, 2006). These observations suggest that the dysregulation of multiple neurotrophic/growth factor systems might be involved in the etiology of mood disorders.…”
Section: Mechanism Of Gdnf Production By Antidepressants 155mentioning
confidence: 99%
“…Recently, both clinical and preclinical animal studies have demonstrated that multiple neurotrophic/growth factors, such as glial cell line-derived neu-rotrophic factor (GDNF), a member of the transforming growth factor ␤ superfamily, have been proposed to play an important role in the therapeutic effect of antidepressants (4,5). Glial cell line-derived neurotrophic factor has been shown to be decreased in the peripheral blood of patients with MDD (6), whereas blood levels of GDNF in MDD are increased after antidepressant treatment (7). These findings suggest that modulating GDNF production may be a key therapeutic effect of antidepressants.…”
Section: Major Depressive Disorder (Mdd)mentioning
confidence: 99%
“…Second, GDNF increases the proliferation of neural progenitors in the adult DG in vivo [11]. Third, the levels of whole blood GDNF in patients with mood disorders are significantly lower than those in healthy control subjects [22]. Fourth, STAT3 might mediate astrogliogenesis from neural precursor cell [23,24,25,26,27] and GDNF-dependent mechanisms might exist for activation of STAT3 [28,29].…”
Section: Introductionmentioning
confidence: 99%